Al-Dakhīl dalam Tafsir Ekonomi Al-Qur’an Kontemporer: Analisis Epistemologis terhadap Metodologi Penafsiran - Andryan Rahmana Riswandi (CV Kalimasada Group, 2026)
This article examines the phenomenon of al-dakhīl in contemporary Qur’anic economic interpretation as an epistemological problem that directly affects the construction of Islamic economics. The scope of the study focuses on a critical analysis of economic interpretations of Qur’anic verses that deviate from the discipline of ulūm al-Qur’ān, particularly due to the dominance of weakly grounded contextual rationalization. This study employs a qualitative method with a library research approach, utilizing descriptive-critical and content analysis of contemporary economic tafsīr works alongside classical and modern Qur’anic scholarship. The findings reveal that al-dakhīl in contemporary economic tafsīr no longer primarily appears in the form of fabricated reports, but rather through the imposition of modern economic theories onto the Qur’anic text without adequate methodological verification. The imbalance between contextualization and tafsīr discipline leads to the normalization of problematic interpretations, thereby blurring the boundary between aṣīl tafsīr and al-dakhīl. This study underscores the necessity of strengthening tafsīr methodology as an epistemological prerequisite for developing Islamic economics grounded in justice, public welfare, and the objectives of Sharī‘ah (maqāṣid al-sharī‘ah).